Assessment of arterial stiffness in chronic obstructive pulmonary disease by a novel method: Cardio-ankle vascular index - Aykan, A.Ç.; Gökdeniz, T.; Boyacı, F.; Gül, İ; Hatem, E.; Kalaycıoğlu, E.; Turan, T.; Bektaş, H.; Çilingir, M.B.; Aykan, D.A.; Ayyıldız, F.; Altun, S. (Herz, 2014)
Background Patients with chronic obstructive pulmonary disease (COPD) have an increased risk of cardiovascular morbidity and mortality. Increased arterial stiffness is associated with the presence and severity of cardiovascular disease. The cardio-ankle vascular index (CAVI) is a new method for assessment of arterial stiffness that is not influenced by blood pressure at the time of measurement and is significantly correlated with the presence and severity of cardiovascular disease. The aim of the present study was to evaluate whether there is an association between the spirometric severity of COPD, according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria, with arterial stiffness as assessed by CAVI. Methods We enrolled 123 patients with COPD (102 men) followed up by the chest medicine outpatient clinics and 35 healthy subjects (26 men). All patients were assessed with spirometry, CAVI, and clinical history. Results Patients with COPD had significantly increased CAVI values compared with control subjects (10.37 ± 2.26 vs. 6.74 ± 1.42, p < 0.001). CAVI was correlated with FEV 1 % predicted, FEV 1 /FVC, and COPD stage (r: − 0.54, p < 0.001; r: − 0.58, p < 0.001 and r: 0.78, p < 0.001, respectively). Multivariate regression analysis showed that CAVI was independently associated with GOLD stages (p < 0.001). Conclusion In this study, we have shown that increased arterial stiffness assessed by CAVI is associated with the spirometric severity of COPD.